Political Life in Japan : Democracy in a Reversible World. - Kishima, Takako (Princeton legacy library., 2014)
To understand how change occurs in politics, we should turn from concentrating on intentional political actions to exploring everyday life, especially marginal frames of mind in which people are open to questioning existing ideas and institutions. In so contending, Takako Kishima offers fresh understandings of contemporary Japanese politicians and the Japanese political process, while she also proposes an innovative method of looking at politics in general. Kishima points out that taken-for-granted values and beliefs are revealed as arbitrary when people experience intrusions of the margina.